PMLA, Publications of the Modern Language Association of America: tomo 64 (1949), tomo 65 (1950), tomo 66 (1951). - Antonio Alatorre (Nueva Revista de Filología Hispánica, 1958)
Se reseñó: Publications of the Modern Language Association of America: tomo 64 (1949), tomo 65 (1950), tomo 66 (1951).